Conflict Resolution Skills of Chinese International Students in the United States - Wang, Zhiwei; Zhu, Qijun; Ke, Dong (Journal of International Students, 2022)
The number of Chinese international students in the United States has dramatically been increasing for the past two decades, while little is known about how these Chinese students handle campus conflicts in the United States. With an interpretative phenomenological research methodology, we invited 10 Chinese students at three different universities in the United States to share their experiences and strategies in resolving campus disputes. Five themes emerged based on the experiences of research participants. The findings strongly indicate that conflict management strategies and styles of Chinese students are significantly shaped by Chinese culture, and Chinese international students are less likely to express their needs and negative feelings. According to findings, this study suggests that more attention and resources of student help centers should be allocated to Chinese international students in the United States for improving their learning experiences.